Growth Respons of Jabon from Different Seed Source on Fertilizer Application on the Ex-mines Site of PT. Kaltim Prima Coal, Sangatta, East Kalimantan - Safriati Safriati; Irdika Mansur (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Mining exploitation activities include opening land activities, topsoil removal, dredging and stockpiling could pose a negative impact to the environment. The impact of mining activities may include the opening of forest canopies and soil layer, soil erosion, sedimentation, decreased fertility and land stability, destruction of wildlife habitat, and the environment contamination for human beings, the loss of plant species diversity, pollution of waterways, and drastic changes as a result of the loss of function of the forest microclimate. By the Indonesian law, mining companies are responsible for the reclamation of their ex-mine sites. Jabon (Anthocephalus cadamba) is a local tree species which can be planted as pioneer tree species on ex-mine sites. It is a fast growing species from the family of Rubiaceae having many uses. Objectives of the research were to observe the effects of different seed source and fertilizer application on the growth of jabon on an ex-mine sites of PT Kaltim Prima Coal at Sangatta, East Kalimantan Province. The results of the research show that jabon seedlings with seed source from Malang are more superior than from Sangatta, and 50 g NPK fertilizer per seedlings increased growth of jabon seedlings significantly.